The Competency, Financial Compensation, Supervision and Performance of the Village Midwives in the Bangli Regency - Ari Adiputri; I Putu Ganda Wijaya; I Nyoman Mangku Karmaya (Universitas Udayana, 2014)
Objectives: To determine the relationship between the performance of village midwives with competency, financial compensation and supervision in the Bangli Regency. Methods: The research is a cross-sectional design with a total sample of 45 midwives of Bangli Regency. Data were collected through interviews by using questionnaires in their village. Dependent variabel is the performance of village midwives. Independent variables of this research were competency, financial compensation and supervision. The data were analyzed by using univariate, bivariate (chi-squared test) and multivariate (logistic regression). Results: The univariate analysis indicates that the performance of village midwives is mostly unfavorable (62.2%). The multivariate analysis indicates that the most significant variable was supervision with OR=25.06 (95%CI: 3.24-193.50). Financial compensation and competency were less significant with OR=13.27 (95%CI: 1.49-118.21) and OR=11.31 (95%CI: 1.45-88.21). Conclusion: Supervision was a more influential factor than financial compensation and competency into increasing the performance of village midwives in the Bangli Regency.